The modern interleukin-1 superfamily: Divergent roles in obesity. Issue 5 (October 2016) - Lee, Man K.S.; Yvan-Charvet, Laurent; Masters, Seth L.; Murphy, Andrew J.
Highlights: Divergent roles of the IL-1 superfamily in metabolic disorders. IL-1β drives obesity-related inflammation. IL-18 functions as an anti-obesity cytokine. IL-33 acts to dampen adipose tissue (AT) inflammation and promote AT beiging. Abstract: Obesity is now recognised as a chronic, low-grade inflammatory disease contributing to insulin resistance, type 2 diabetes (T2D) and cardiovascular disease (CVD). Multiple mechanisms leading to the low grade inflammation in this setting have been suggested. Due to the complexity and interconnection of inflammatory and metabolic responses, there also remains a need to fully elucidate the inflammatory mechanisms that control obesity and associated metabolic disorders. One important avenue in the field that has gained great attention is the interleukin (IL)-1 superfamily of cytokines that consist of IL-1β, IL-18 and IL-33. IL-1β is well known for its contribution as an inflammatory mediator in obesity contributing to insulin resistance and T2D, whereas the IL-18 and IL-33 cytokines have been shown to oppose metabolic dysregulation. This review will focus on the current understanding of the IL-1 superfamily of cytokines in the setting of obesity and discuss how endogenous feedback loops can be exploited for therapeutic approaches to fight obesity and subsequent cardiometabolic disorders.